2017
DOI: 10.1186/s13034-017-0174-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of young offenders: a national register-based follow-up study of 15- to 19-year-old Finnish delinquents referred for forensic psychiatric examination between 1980 and 2010

Abstract: BackgroundThe mortality rate of young offenders is high. Furthermore, mortality in young offenders is associated with psychiatric and substance use disorders. The primary aim of this national register-based follow-up study was to investigate the mortality rate of Finnish delinquents who underwent a forensic psychiatric examination between 1980 and 2010. As delinquency is not a solid entity, we further aimed to compare the risk of premature death among different subgroups of the delinquents; violent versus non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Although all these models can account for some cases of premature deaths among offenders, many recent studies have indicated a lack of direct connection between early mortality and breaking the law (Tremblay and Paré 2003;van de Weijer et al 2016;Zane et al 2018). Most of all, compared with the general population, offenders are more likely to die from unnatural causes (Chen et al 2010;Elonheimo et al 2017) such as accidents (Lindberg et al 2017;Rosen et al 2008;Zane et al 2018), suicide (Björk and Lindqvist 2005;Lindqvist et al 2007), and as a result of substance abuse (Bukten et al 2017;Forsyth et al 2014). Moreover, an analysis of data obtained from the National Longitudinal Study of Adolescent Health has shown that adolescents with a pessimistic outlook on their life expectancy are more likely to engage in criminal activity later in life (Nedelec and Beaver 2012).…”
Section: Life History Strategies Of Men At Risk Of Premature Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…Although all these models can account for some cases of premature deaths among offenders, many recent studies have indicated a lack of direct connection between early mortality and breaking the law (Tremblay and Paré 2003;van de Weijer et al 2016;Zane et al 2018). Most of all, compared with the general population, offenders are more likely to die from unnatural causes (Chen et al 2010;Elonheimo et al 2017) such as accidents (Lindberg et al 2017;Rosen et al 2008;Zane et al 2018), suicide (Björk and Lindqvist 2005;Lindqvist et al 2007), and as a result of substance abuse (Bukten et al 2017;Forsyth et al 2014). Moreover, an analysis of data obtained from the National Longitudinal Study of Adolescent Health has shown that adolescents with a pessimistic outlook on their life expectancy are more likely to engage in criminal activity later in life (Nedelec and Beaver 2012).…”
Section: Life History Strategies Of Men At Risk Of Premature Deathmentioning
confidence: 99%
“…The tendency to engage in criminal activity is commonly associated with low life expectancy (Aalsma et al 2016 ; Lindberg et al 2017 ). There are three models of explanation for premature mortality among offenders that are not mutually exclusive (van de Weijer et al 2016 ).…”
Section: Life History Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the Unites States, little is known on the risk of dying from violence among justice-involved young people. Similar to trends in the general population (Grinshteyn & Hemenway, 2016), studies conducted in Australia (Coffey et al, 2004) and Finland (Lindberg et al, 2017;Sailas et al, 2006) found that a lower proportion of young people released from detention died from violence (3%-16%) compared to U.S.-based studies (48%-68%) (Aalsma et al, 2016;Ezell & Tanner-Smith, 2009;Teplin et al, 2014). Our previous study found that violence-related deaths among justice-involved young people in Australia often involved a weapon, were preceded by an altercation for men and a relationship breakdown for women, and had cannabis and/or alcohol present in the toxicology reports of the death (Willoughby et al, 2021).…”
Section: Introductionmentioning
confidence: 57%
“…Juvenile delinquents have, as a group, a long history of low academic achievement and an incongruent, poorly reflected appraisal (Blomberg & Pesta, 2017;Walters, 2020). Much higher rates of mental illness compounded the problem of poor educational attainment (Lindberg et al, 2017). Once released, juvenile delinquents have behavioral problems in school and a much higher rate of dropping out of high school (Benner et al, 2016;Jaggers et al, 2016).…”
Section: Literatumentioning
confidence: 99%